Dare to love a duke ebook The london underground. - Leigh, Eva (London Underground, 2018)
Named one of Amazon's Best Romances of December! For a dashing duke and the proprietress of a secret, sensual club in the London Underground, passion could lead to love... if they dare Thomas Powell, the new Duke of Northfield, knows he should be proper and principled, like his father. No more dueling, or carousing, or frequenting masked parties where Londoners indulge their wildest desires. But he's not ready to give up his freedom just yet. The club is an escape, a place where he can forget about society and the weight of his title... and see her, the woman he's wanted forever. Lucia—known as Amina—manages the Orchid Club, a secret society where fantasies become reality. But for Lucia, it's strictly business, profitable enough to finance her dream: a home for the lost girls of the streets. Surrounded by lovers, she only observes, unwilling risk her future for any man. No member has ever intrigued her...until him, the masked stranger whose heated looks sear her skin. After months of suppressed longing, they dare to give in to temptation... But the late duke's legacy comes with a shocking secret, and the scandal threatens to destroy everything Tom loves... his family, the Orchid Club, and even Lucia.